Analisis Perbedaan Return Saham Sebelum dan Sesudah Hari Libur Akhir Tahun - Revo Gilang Firdaus; Reza Sabto Helty (P4M STIE Putra Bangsa, 2021)
Stock returns experience movements based on fluctuating stock prices. This research aims to identify whether there is a disparity in stock returns before the year-end holidays and after the end of the year on the Indonesia Stock Exchange. This research method is carried out by collecting data on stock prices before the end of the year and stock prices after the end of the year from December 2016 to January 2021 by taking daily data (closing prices). The method of analysis used was SPSS software with descriptive statistics, normality test using Kolmogorov-Smirnov, and t test by using Paired Sample t-test. The outcome exhibit that the data were normally dispersed with the value of Asymp. Sig. 2-tailed of 0.200. In addition, the results of the hypothesis test with the t test resulted in a significance value of 0.636. This research indicates that there is no significant contrast in stock returns before & after the year-end holidays.